2020
DOI: 10.17261/pressacademia.2020.1186
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the technology acceptance model (TAM) in information management research: a review of selected empirical evidence

Abstract: Purpose-The purpose of the study was to examine the relevance of the Technology Acceptance Model (TAM) in information management research, and how it has been extended in relation to its perceived usefulness and perceived ease of use. Methodology-A desk study approach was used to review some of the studies that have used the model. Search engines, such as google scholar, yahoo search, and answers. com, were used to search through internationally renowned journals like Emerald, Science direct, IJRIC, South Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 13 publications
2
14
0
1
Order By: Relevance
“…Kemudahan penggunaan bisa jadi bermakna relatif pada masing-masing user. Karena kemudahan akan dirasakan user seiring dengan frekuensi pengalaman menggunakan suatu software, kemudahan ditentukan oleh pengalaman (Enu-Kwesi & Opoku, 2020;Choi & Chung, 2012;Ma & Liu, 2005) maka kemudahan bukanlah faktor yang mempengaruhi user untuk menggunakan suatu software. Penelitian ini membuktikan bahwa dengan meningkatnya pengalaman langsung dengan suatu sistem, pengguna akan memiliki lebih banyak informasi tentang seberapa mudah atau sulitnya sistem digunakan.…”
Section: Discussionunclassified
“…Kemudahan penggunaan bisa jadi bermakna relatif pada masing-masing user. Karena kemudahan akan dirasakan user seiring dengan frekuensi pengalaman menggunakan suatu software, kemudahan ditentukan oleh pengalaman (Enu-Kwesi & Opoku, 2020;Choi & Chung, 2012;Ma & Liu, 2005) maka kemudahan bukanlah faktor yang mempengaruhi user untuk menggunakan suatu software. Penelitian ini membuktikan bahwa dengan meningkatnya pengalaman langsung dengan suatu sistem, pengguna akan memiliki lebih banyak informasi tentang seberapa mudah atau sulitnya sistem digunakan.…”
Section: Discussionunclassified
“…While some studies found the TAM to be beneficial in predicting and evaluating customers' technology usage habits over time, others criticized it for being too restricted in terms of theoretical assumptions and actual usefulness. The model, according to these critiques, lacks the necessary qualities to be a competent theory for information system research [24]. Furthermore TAM lacks control factors like as age, gender, and experience all have an impact on how people view technology and, as a result, how it is viewed [25,26].…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…are what are referred to as external factors in this model (Lin, et al 2011). The component of perceived usefulness in the technology acceptance model refers to a degree to which the computer system user believes that the use of the system will increase his/her performance (Opoku, 2020). In general, the said model focuses on a computer user with a perceived usefulness concept aimed at explaining the way users perceive usefulness.…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%